İstanbul Üniversitesi Nadir Eserler Kütüphanesi TY03715 Numarada Kayıtlı Mecmû’a-i Eş’âr (İnceleme-Metin) - Yavuz, Buse (Fatih Sultan Mehmet Vakıf Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2022)
Bu çalışmada İstanbul Üniversitesi Nadir Eserler Kütüphanesi TY03715 numarada kayıtlı şiir mecmuası incelenip transkripsiyonlu metin yapılmıştır. Mecmua, 69 varaktan meydana gelmiş olup tespit edilen 84 şair ve 460 şiir bulunmaktadır. Çalışmamız üç bölümden oluşmaktadır. İlk bölümde mecmuanın tanımı ve klasik Türk edebiyatında mecmuanın önemi hakkında bilgiler verilmiştir. İkinci bölümde çalışmamıza konu olan mecmua şekil ve muhteva yönüyle incelenmiştir. Şairlerin kısa biyografileri, metinde imla kusurları ve muhteva hususiyetleri yer verilmiştir. Üçüncü bölümde ise transkripsiyonlu metni hazırlarken takip ettiğimiz yöntem hakkında bilgi verilip metin sunulmuştur.

In this study, the poetry collection registered in Istanbul University Rare Works Library with no. TY03715 was examined and the transcripted text was made. The journal consists of 69 leaves and there are 84 poets and 460 poems identified. Our work consists of three parts. In the first part, information about the definition of the journal and the importance of the journal in classical Turkish literature are given. In the second part, the journal, which is the subject of our study, has been examined in terms of form and content. Short biographies of the poets, spelling errors in the text and content features are included. In the third chapter, information about the method we followed while preparing the transcripted text is given and the text is presented.
Istanbul University Rare Works Library Mecmû’ai Eş’âr That is Registered to Ty03715 (Examination-text)
Keywords: Klasik Türk Edebiyatı; Mecmua; Şair; Şiir; Şiir Mecmuası; Classical Turkish Literature; Journal; Poetry; Poem; Poetry Collection